Hospital-based incidence of traumatic spinal cord injury in tehran, iran. - Mahdi Sharif-Alhoseini; Vafa Rahimi-Movaghar (Tehran University of Medical Sciences, 2014)
The goal of this study was to describe the hospital-based incidence of traumatic spinal cord injury in Tehran, Iran.We retrospectively reviewed the hospital records of traumatic spinal cord injury patients, admitted between March 2010 and July 2011 in 61/68 hospitals of Tehran.Overall, 138 cases of traumatic spinal cord injury were identified. The majority of patients were male (84.8%). The mean age was 33.2 ± 14.3 years. 54.3% patients were residing in Tehran and the others were referred from other cities. The mean annual incidence of hospitalized traumatic spinal cord injury patients of Tehran was 10.5/1,000,000/year (95% confidence interval: 9-12). Fall was the leading cause of injury (45.7%), followed by road traffic crash (40.6%). The most common cause of tetraplegia (cervical traumatic spinal cord injury) was road traffic crash. The duration of hospital stay for tetraplegia and paraplegia (thoracic and lumbar traumatic spinal cord injury) was 22.7±23.7 and 12.5±7.5, respectively (P